Recipient-derived IL-22 alleviates murine acute graft-versus-host disease in association with reduced activation of antigen presenting cells. (November 2018) - Pan, Bin; Xia, Fan; Wu, Yujing; Zhang, Fan; Lu, Zhenzhen; Fu, Ruixue; Shang, Longmei; Li, Lingling; Sun, Zengtian; Zeng, Lingyu; Xu, Kailin
Highlights: Knock out of IL-22 in recipients aggravates hepatic and intestinal aGVHD. IL-22 mediates activation of dendritic cells. Recipient-derived IL-22 regulates polarization of Th1 cells and Tregs in aGVHD. Abstract: Acute graft-versus-host disease (aGVHD) remains a major challenging complication of patients receiving allogeneic hematopoietic cell transplantation (allo-HCT). CD4 + effector T cells and their related cytokines mediate pathogenesis of aGVHD, in which donor-T-cell derived interleukin-22 (IL-22) was recently indicated to play a role. The role of recipient-derived IL-22 in aGVHD remains to be elucidated. By applying IL-22 knock out (IL-22KO) mice as recipients of allotransplant, we found recipient derived IL-22 alleviated aGVHD and improved survival of allotransplant recipients. Knock out of IL-22 in recipient increased levels of T-helper (Th1) 1 cells but decreased levels of regulatory T cells (Tregs) in target tissues of aGVHD. Levels of IL-22 increased in aGVHD mice. Recipient antigen presenting cells (APCs) are important sources of IL-22. IL-22 reduced activation of APCs in vitro . Defect of IL-22 in APCs resulted in increased polarization of Th1 cells but decreased level of Tregs in an in vitro co-culture system. Our data highlight an immunoregulatory function of recipient-derived IL-22 in aGVHD.